Early and late clinical outcomes and cost-effectiveness of aortic valve replacement using the Inspiris Resilia bioprosthesis - Ahmed Ahmed; Tarek A. Abdel Aziz; Mohannad M. R. AlAsaad; Motaz Majthoob; Kamaleldin Ahmed Altahmody (Journal of Cardiothoracic Surgery)
Abstract Background The present study aimed to critically revise the published literature on clinical outcomes and cost-effectiveness of Inspiris Resilia valve. Methods This work was conducted according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Full text research articles discussing clinical or cost-effectiveness aspects of Inspiris Resilia bioprosthesis published in English were included in this analysis. Studies were excluded if they weren’t exclusively conducted on patients submitted to surgical aortic valve replacement using the Inspiris Resilia bioprosthesis. Results The technical success rate was almost perfect in all studies. Reported complications included severe prosthesis-patient mismatch, reoperation, endocarditis, and paravalvular leak. In almost all studies, there were significant improvement of NYHA at the end of follow up as compared to baseline. In all studies, there were significant improvement of one or more hemodynamic parameters at the end of follow up as compared to baseline. Conclusions Surgical aortic valve replacement using Inspiris Resilia tissue valve appears to be safe and effective with low rate of aortic valve and systemic complications and mortality. Its performance appears to be equal to or better than many other bioprosthetic valves. As compared to mechanical valves, its use is suggested to be more cost-effective.